A Retrospective Study of Small Animal Poisoning at the Veterinary Medical Teaching Hospital from South Region of Brazil - Zang, Luciana; Bing, Rafaela Scheer; de Araujo, Ana Cristina Pacheco; Ferreira, Marcio Poletto (Acta Scientiae Veterinariae, 2018)
Background: Poisoning cases are a challenge for the veterinary practitioner, since many agents can be involved. The incomplete patient history associated with advanced poisoning stage often leads to death. Since lacking information is common, it is essential to be aware of principal poisoning agents and their associated symptomatology. The aim of this study is to describe the major agents involved in small animal poisoning, the causative agent, poisoning route, time to search veterinary care, clinical signs and ancillary tests of canine and feline patients treated at the Veterinary Medical Teaching Hospital from January 2010 to June 2016. Materials, Methods & Results: Forty-four medical records with poisoning history were found and reviewed, but only 30 medical records had complete data to be evaluated. There were 24 dogs and 6 cats, 17 female and 13 male. Six females were spayed. Poisoning agent identification was possible in 29 cases and was food, molluscicide, cleaning product, ornamental plants, medication, rodenticide and antiparasitic drugs. Fourteen poisonings were caused by the owner and 16 were accidental. There was a higher poisoning incidence in dogs than cats. Most of the patients were young and unneutered/unspayed. Discussion: In this study there was a higher poisoning prevalence in dogs than cats, as occurred in other studies published in Europe, Belgium, France, Greece, Italy, Spain, Austria and other Brazilian regions. Most of the patients were young, which is in agreement with previous studies in which young animals were more affected. Domestic antiparasitic drugs were the most common poisoning agents (33%), as reported in studies from France and Spain. In southern Brazil, the most common poisoning agent was medication, whereas in southeast Brazil, organophosphates were the most prevalent poisoning agent. Considering this, the geographic localisation seems to influence the poisoning agent. It is known that many owners give unprescribed medication to their pets and this also happened in this study, as 46% of the poisoning cases were caused by the owner. The most common clinical signs were gastrointestinal (76%, emesis and anorexia) and neurological (63%, depression). This is in agreement with another study that showed a high number of patients poisoned by medications leading to severe gastrointestinal clinical signs. Despite a history of eating spiced food, our food-poisoned patient did not show clinical signs compatible with pepper poisoning. In fact, clinical signs were more compatible with salt or onion and garlic poisoning, but there was no history to support that our patient had eaten these foods. The patient who ate fern and busy Lizzie (Impatiens walleriana) did not show clinical signs compatible with these agents but showed gastrointestinal clinical signs that could have occurred due to plant indigestion. This fact emphasises the need for more studies in this area. One dog with rodenticide poisoning presented with normal blood test results, but the blood sample was collected a few hours after exposure. This can occur after brodifacoum poisoning, which has a longer half-life than warfarin. In brodifacoum poisoning cases, clinical signs can appear days after exposure. In one dog, it was not possible to indentify the poisoning agent and this specific patient case exemplifies the challenge to diagnose the exact poisoning agent and concomitant diseases when the history is incomplete. This retrospective study shows the heterogeneity of the causative agents and the associated symptomatology, which highlights the need for further studies in this area. In this study, antiparasitic drugs were the most common poisoning agents, especially pyrethroids. Dogs were more affected than cats. Most of the patients were young and unneutered/unsprayed, indicating these characteristics could be a risk factor in this study.